Halting the Digital Equity Act: Stop-Work Order on Bridge for Digital Divide - Kara Malenfant (The Political Librarian, 2025)
This opinion piece frames the Trump administration’s attempt to abruptly cancel the Digital Equity Act (DEA) as one critical battle in a much larger war to restrict access to information and limit education. In seeking to halt the DEA’s historic expenditures of 2.75 billion to ensure improved broadband adoption, inclusion, and digital skills, the administration aims to perpetuate the well-documented and long-recognized digital divide. Because greater availability does not necessarily translate to greater use, adoption requires support from the “human infrastructure of broadband” (Rhinesmith and Prasad 2025), with library and information science (LIS) workers playing valuable roles. This piece maintains that access to information in all formats is both a human right and a core professional value and that the educational role of librarians in lifelong learning and information literacy (including digital literacy) constitutes a set of professional competencies and guiding principles. It contends that library workers should share our commitment to digital equity and inclusion whenever we rally around professional values and principles to advocate for our communities. As LIS workers unite to uphold information access, foster diversity and inclusion, promote lifelong learning, and improve literacy, we must assert the vital role of libraries as community anchor institutions and our own roles as educators in the digital world. <!–EndFragment–>
Keywords: broadband adoption; broadband use; digital divide; digital equity; digital inclusion; digital literacy; information policy